Manganese-Catalyzed α-Trideuteromethylation of Sulfones - Li, Guanbo; Liu, Weiping (Synlett, 2025)
Recent advancements in deuteration techniques have garnered significant attention from both academia and industry. Herein, we report a manganese-catalyzed α-trideuteromethylation of sulfones with CD3OD as a deuterating reagent via a deuterium autotransfer strategy under mild conditions. Our approach yields target compounds with 60–96% efficiency and deuteration levels up to 99%. This methodology stands out due to its reliance on accessible deuterium sources, an earth-abundant transition-metal catalyst, and mild conditions.
Keywords: manganese; homogeneous catalysis; deuterated methanol; α-trideuteromethylation; deuterium autotransfer